Food Products with Mesocarp Babassu: A Review - Veronica Cardoso De Souza, Barbara; dos Reis Moreira-Araujo, Regilda S.; Morais Vieira Galvao, Luanne; de Carvalho Vale, Larice; de Moura Rocha, Lindalva; Larissa Sousa Cardoso, Monica; Gabriela Costa Lima Porto Luz, Rayssa; Fabricia Beserra Goncalves, Maria; Almeida Silva, Oskar; Cesar Cunha Nunes, Livio (Current Nutrition & Food Science, 2018)
The babassu palm is one of the most important representatives of the palm family in Brazil. The almond and mesocarp are the edible parts of the babassu, used in human food, animal and as medicine. Due to the fact that the babassu mesocarp is rich in starch and other nutrients, the objective of this work was to carry out a technological survey on the use of the mesocarp of babassu in the elaboration of food products such as biscuits, breads and cereal bars. The search for deposited patents was carried out in the databases of the National Institute of Industrial Property (INPI), the European Patent Convention (EPO), the United States Patent and Trademark Office (USPTO) and the World Intellectual Property Organization (WIPO). The database for the search for scientific articles was the Web of Science. When the
Keywords: foods